Carbon nanomaterials as an environmental technology in the remediation of agricultural soils contaminated with heavy metals: a review - María Sol-Magdaleno; José Ignacio Aguilar-Aguilar; Elías Beltrán-Naturi; Luis Dorian Valencia-Ordóñez; Amílcar Díaz-González; Pedro Trejo-Flores; César Augusto Camas-Flores; Gabriela Palacios-Pola; Zulfiqar Ali-Sahito; Magín González-Moscoso (Discover Soil)
Abstract Heavy metals are inorganic contaminants derived from natural and anthropogenic sources that cause damage to ecosystems. Various environmental technologies, both chemical and biological, have been used to remediate soils impacted by these pollutants. Currently the use of nanotechnology through carbon nanomaterials has attracted attention for its ability to immobilize heavy metals in soil. The objective of this review was to explore the potential of carbon-based nanomaterials as an innovative technology for the remediation of soils contaminated with heavy metals. In this review, we used major scientific databases as our source of scientific literature and selected recent articles on heavy metals, soil remediation, carbon nanomaterials, and their applications in nanoremediation. We found that heavy metals are toxic to soil microorganisms and plants, can damage metabolic processes, leading to cell death. These contaminants can easily enter the food chain through food produced in agricultural fields, posing a risk to human health. We have found that carbon-based nanomaterials can immobilize and reduce the translocation of heavy metals and have potential as remediators of soil contamination. Furthermore, based on available data, there are few scientific reports on the use of carbon-based nanomaterials for the remediation of heavy metal soils. While every environmental technology for the remediation of soils contaminated with heavy metals has its advantages and disadvantages, the development of carbon nanomaterials offers a novel alternative as a control and remediation measure for heavy metals that has a great future in environmental protection.